Phenotyping in the era of genomics: MaTrics—a digital character matrix to document mammalian phenotypic traits - Clara Stefen; Franziska Wagner; Marika Asztalos; Peter Giere; Peter Grobe; Michael Hiller; Rebecca Hofmann; Maria Jähde; Ulla Lächele; Thomas Lehmann; Sylvia Ortmann; Benjamin Peters; et al. (Mammalian Biology, 2022)
A new and uniquely structured matrix of mammalian phenotypes, MaTrics ( Ma mmalian Tr aits for Comparative Genom ics ) in a digital form is presented. By focussing on mammalian species for which genome assemblies are available, MaTrics provides an interface between mammalogy and comparative genomics. MaTrics was developed within a project aimed to find genetic causes of phenotypic traits of mammals using Forward Genomics. This approach requires genomes and comprehensive and recorded information on homologous phenotypes that are coded as discrete categories in a matrix. MaTrics is an evolving online resource providing information on phenotypic traits in numeric code; traits are coded either as absent/present or with several states as multistate. The state record for each species is linked to at least one reference (e.g., literature, photographs, histological sections, CT scans, or museum specimens) and so MaTrics contributes to digitalization of museum collections. Currently, MaTrics covers 147 mammalian species and includes 231 characters related to structure, morphology, physiology, ecology, and ethology and available in a machine actionable NEXUS-format*. Filling MaTrics revealed substantial knowledge gaps, highlighting the need for phenotyping efforts. Studies based on selected data from MaTrics and using Forward Genomics identified associations between genes and certain phenotypes ranging from lifestyles (e.g., aquatic) to dietary specializations (e.g., herbivory, carnivory). These findings motivate the expansion of phenotyping in MaTrics by filling research gaps and by adding taxa and traits. Only databases like MaTrics will provide machine actionable information on phenotypic traits, an important limitation to genomics. MaTrics is available within the data repository Morph·D·Base ( www.morphdbase.de ).

Aberrant splicing in MLH1 and MSH2 due to exonic and intronic variants - Constanze Pagenstecher; Maria Wehner; Waltraut Friedl; Nils Rahner; Stefan Aretz; Nicolaus Friedrichs; Marlies Sengteller; Wolfram Henn; Reinhard Buettner; Peter Propping; Elisabeth Mangold (Human Genetics, 2006)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)